2022
DOI: 10.13057/biodiv/d231044
|View full text |Cite
|
Sign up to set email alerts
|

Identification of culture-dependent microbes from mangroves reveals dominance of Bacillus including medically important species based on DNA signature

Abstract: Abstract. Dechavez R, Calub ML, Genobata DR, Balacuit R, Jose R, Tabugo SR. 2022. Identification of culture-dependent microbes from mangroves reveals dominance of Bacillus including medically important species based on DNA signature. Biodiversitas 23: 5342-5350. Mangroves are among the most crucial plant hosts in the marine environment because of their notable role in the ecosystem and their benefits. Identification of plant-associated and culture-dependent microbes is key to having a rich reservoir of bioacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
(23 reference statements)
2
2
0
Order By: Relevance
“…Proteobacteria was the second most abundant phylum, primarily represented by the class Gamma-proteobacteria. This finding is consistent with some previous studies [ [46] , [47] , [48] ] but differs from others that reported Proteobacteria as the dominant phylum in leaf endophytic bacteria [ 49 , 50 ]. Among the fungal isolates, the majority belonged to the phylum Ascomycota (90%), with classes Sordariomycetes (35%) and Dothideomycetes (30%) being the most represented.…”
Section: Discussionsupporting
confidence: 91%
“…Proteobacteria was the second most abundant phylum, primarily represented by the class Gamma-proteobacteria. This finding is consistent with some previous studies [ [46] , [47] , [48] ] but differs from others that reported Proteobacteria as the dominant phylum in leaf endophytic bacteria [ 49 , 50 ]. Among the fungal isolates, the majority belonged to the phylum Ascomycota (90%), with classes Sordariomycetes (35%) and Dothideomycetes (30%) being the most represented.…”
Section: Discussionsupporting
confidence: 91%
“…When assessing the alpha diversity of the bacterial community using the Shannon index, it was observed that S. alba displayed the highest diversity, with a value of 2.75 among all the mangrove species examined (Figure 3). Results were consistent with previous studies where S. alba consistently exhibits the highest diversity in microbial communities (Muwawa et al 2021;Dechavez et al 2022). The genus Sonneratia is often found in river estuaries and can thrive in environments characterized by high environmental stress and poor conditions ).…”
Section: Alpha Diversitysupporting
confidence: 91%
“…These processes encompass methanogenesis, phosphate solubilization, sulfate reduction, and the synthesis of various compounds like antibiotics and enzymes (Wu and Lu 2015). Notably, genera like Serratia and Stenotrophomonas have been found to participate in the nitrogen cycle and carbon dioxide fixation (Dechavez et al 2022;Meng et al 2022). These nitrogen-fixing bacteria inhabit the rhizosphere and decompose leaves, pneumatophores, and mangrove sediments (Zhang et al 2017a), where the denitrification process occurs, converting nitrates into nitrogen.…”
Section: Identification Of Bacterial Communitiesmentioning
confidence: 99%
“…Mangrove habitat is a productive source of endophytic microorganisms. Mangroves' roots and leaves serve as a habitat for many bacteria, fungi, and algae [2]. The benefits of mangroves for human life are to cure muscle pain, back pain, rheumatic malaria, wounds, tuberculosis and spermicides and benefits for the environment [3].…”
Section: Introductionmentioning
confidence: 99%